Arterial oxygen saturation profiles in healthy preterm infants. Issue 1 (1st July 1998) - Ng, A; Subhedar, N; Primhak, R A; Shaw, N J
Abstract : AIM: To construct a reference range of SpO2 values in healthy preterm infants using a simple data logging device. METHODS: Thirty three healthy preterm infants were monitored for a continuous period of 4 hours at rest using an Ohmeda Biox 3700 E Pulse Oximeter and an electronic data logger (Rustrack Ranger). Stored data were downloaded and saved as individual files on a personal computer. RESULTS: The study group median and 5th and 95th percentiles were used to construct a cumulative frequency curve of time against SpO2 value, representing the normal reference range of SpO2 profiles in healthy preterm infants. CONCLUSION: Comparison of an infant's SpO2 profile against this curve may be more helpful in guiding supplemental oxygen treatment in that individual than a figure for a mean SPO2 and its standard deviation.